A quality based framework to challenge Development Aid Management: defies derived from Human Resource cultural background tension - Justen Nosoliny, João L. Serras Pereira (Africana Studia, 2020)
In order be able to compete, south Mediterranean and overall African SMEs do need to attain international quality levels for their products and services. In an industrial environment they need to be included in several supply chains and address the requirements of different suppliers and clients. The SME will then belong to a number of “extended enterprises” which may have several different requirements and company staff must dynamically learn and adapt to different environments. Thus, rolling training is required, and a ISO 15504 CMM – Capability Maturity Model based process, supported on proved and documented best practices was derived for the aeronautical and automotive industries, a number of data points acquired and, from the model, a self-assessment tool was built so staff may improve their skills whilst operating at several supply chains. In this paper we present the overall results attained, the building of the self-assessment tool and the set of keystone findings. Keywords: self-assessment, life-long learning, best practices, competitiveness.